(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this paper is to increase the heat exchange rate in the monolithic heat exchanger by changing the air passage shape and materials; here we used circular, hexagonal, oval shape for air passage and Al2O3, SiC CrCO3 ceramic materials for our research work. The heat flow rate is analyzed in CFD fluent software and model in done in CATIA software.